Synchronization and Antisynchronization of N-Coupled Complex Permanent Magnet Synchronous Motor Systems with Ring Connection - Cuimei Jiang; Shutang Liu (Complexity)
This paper discusses synchronization and antisynchronization of N-coupled complex permanent magnet synchronous motors systems with ring connection. Based on the direct design method and antisymmetric structure, the appropriate controllers are designed to ensure the occurrence of synchronization and antisynchronization in an array of N-coupled general complex chaotic systems described by a unified mathematical expression with ring connection. The proposed method is flexible and is suitable both for design and for implementation in practice. Numerical results are plotted to show the rapid convergence of errors to zero and further verify the effectiveness and feasibility of the theoretical scheme.